Preconceito linguístico e a formação de crenças - VILHENA, Naiza Sena de (2019)
The present work was developed with the objective of investigating the influence of linguistic prejudice in the formation of beliefs about learning Portuguese. This research was carried out with five students from the 7th year of Elementary School. The instrument used was a semistructured interview, organized from 10 questions related to the specific objectives that seek to investigate the social origin of the students, to the difficulties found in the Portuguese Language discipline, to highlight possible beliefs about the discipline and the manifestation of linguistic prejudice in the school and family environment. As a theoretical contribution, this work is based on the precepts of Bagno (2003, 2007, 2009, 2014, 2015), Barcelos (2007), Botassini (2013, 2015) and Possenti (1997, 2010). The data reveal that the students with the greatest difficulty in Portuguese Language belong to the lower social class, which consequently distances them from the standard language taught by the school and justifies greater difficulty in reading and writing. It was also identified the belief that knowing Portuguese is related to the domain and knowledge of grammatical rules. The results also reveal that all students have already suffered linguistic prejudice, both in the school environment and in the family environment. However, these students do not have the perception that they are suffering discrimination because of their way of speaking.